FEATURES INSTITUTIONALIZATION OF POLITICAL PARTIES IN UKRAINE (ON THE EXAMPLE IVANO-FRANKIVSK OBLAST) - Климончук, В. Й. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article, becoming of the party system is considered on Prykarpattya. The process of institutionalization of multi-party is analysed in Ukraine in intercommunication with the stages of processes of public transformation. An author pays attention on creation of socio-political terms for party structuring of local representative authorities, strengthening of responsibility of political parties for activity of local-authority and increase of their role in an acceptance and realization of political decisions. It becomes firmly established that due to party mechanisms there is structuring of local elites, making by them the concerted strategies of behavior. It will be that under act of commercialization of parties a valued-ideological factor without that there can not be parties in their traditional understanding loses his decision value. It is marked that the present system of economic relations and mental features of citizens predetermine the processes of increase of commercialization of electoral activity.